The Influence of Digital Leadrrship and Digital Competence on Employee Performance Mediated by Job Satisfaction in Health Services in Tarakan City - Ulum, Bahriyahtul; Wulansari, Puspita (Eastasouth Institute, 2025)
This study examines the effect of digital leadership and employee digital competence on employee performance in health services in implementing One Healthy with job satisfaction as a mediating variable in Tarakan City. The implementation of the health transformation launched by the Ministry of Health requires the ability of health workers to implement health data digitization by carrying out digital recording of patient health examination results. This research design uses quantitative and descriptive methods. The participants in the study were health workers at the Puskesmas who played a role in the implementation of recording patient medical record data into the Satu Sehat platform. The sample in this study amounted to two hundred and two health workers at six Puskesmas in Tarakan City. The research strategy used a random sampling method with primary data sources by distributing questionnaires. The results showed that digital leadership and digital competence had no direct effect on performance. The role of job satisfaction as a mediating variable is able to provide a positive influence from digital leadership and digital competencies on employee performance in Tarakan City health services.